Employee Net Promoter Score (eNPS) as a Single-item Measure of Employee Work Satisfaction An Empirical Evidence from Companies Operating in Poland - Sedlak, Piotr (Contemporary organisation and management. Challenges and trends, 2020)
The goal of the article was to evaluate the pros and cons of using the eNPS indicator and its possible adaptation in employee satisfaction surveys.The author conducted 3 independent surveys on over 6500 employees in 3 different companies. The eNPS results were correlated with questions concerning the general opinion about work and the employer.The eNPS indicator was proven to highly correlate with items describing the general employee opinion about work satisfaction. The numerical value of the indicator itself is considered by the author as misleading due to asymmetry in the classification of positive and negative opinions.